Development of Management Tools Based on the Determination of Indexes - Barrantes Jiménez, Roy (2025)
In order to answer to the express need to establish tools that were capable of offering support for the eventual creation of an Asset Management System in Costa Rica, the Research Unit of the Lanamme UCR developed a methodology that allows to define strategies of intervention in the network level for the main road network in Costa Rica. This methodology is based on a modification of the VIZIR method, developed by the Central Laboratory of Bridges and Roads (France, 1972) and used by the Sectorial Planning Department of Costa Rica since 1995 and based also on the definition of homogeneous sections by the International Roughness Index (IRI). With this methodology it was possible to calculate for each IRI's homogeneous section other important indexes, such as the Present Serviciability Index (PSI), the Pavement Condition Index (PCI), the quality notes Q (from VIZIR) and typical values of deflections for every section, depending on the average daily traffic (TPD) on each one. With this complete database of Information, it was possible to establish, in each homogeneous section, a specific strategy of intervention such as maintenance, structural reinforcement or reconstruction, all this information was taken to maps in a geographical Information system for easy managing and updating.